2018
DOI: 10.1111/jphp.12990
|View full text |Cite
|
Sign up to set email alerts
|

Oral deferiprone administration ameliorates cisplatin-induced nephrotoxicity in rats

Abstract: The results supported a role for iron in cisplatin-induced nephrotoxicity and TfR may serve as an important source of iron. Based on these findings, deferiprone pretreatment may play a role in preventing cisplatin-induced nephropathy in cancer patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 64 publications
(157 reference statements)
0
7
0
Order By: Relevance
“…We showed that antiferroptotic drugs ameliorated cisplatin-induced AKI and LPS/GalN-induced liver injury. In previous reports, iron chelators prevented lipid peroxidation and ameliorated renal damage in cisplatin nephrotoxicity, 53,54 also suggesting that ferroptosis is involved in the pathophysiology of cisplatin-induced AKI. Although, in this study, the renoprotective effect of Fer-1 was not statistically significant in the cisplatin model (Supplemental Figure 6), recent studies showed that the antiferroptotic effect of Fer-1 is not potent in in vivo conditions, unlike its high activity in vitro, because of its instability in plasma.…”
Section: Discussionmentioning
confidence: 76%
“…We showed that antiferroptotic drugs ameliorated cisplatin-induced AKI and LPS/GalN-induced liver injury. In previous reports, iron chelators prevented lipid peroxidation and ameliorated renal damage in cisplatin nephrotoxicity, 53,54 also suggesting that ferroptosis is involved in the pathophysiology of cisplatin-induced AKI. Although, in this study, the renoprotective effect of Fer-1 was not statistically significant in the cisplatin model (Supplemental Figure 6), recent studies showed that the antiferroptotic effect of Fer-1 is not potent in in vivo conditions, unlike its high activity in vitro, because of its instability in plasma.…”
Section: Discussionmentioning
confidence: 76%
“…It has been reported that the exposure of humans and animals to certain metals or metal-containing compounds leads to toxic and carcinogenic effects like neurotoxicity, hepatoxicity, and nephrotoxicity. , However, several vital transition metals, such as Fe, copper (Cu), zinc, manganese, and cobalt (Co) have an important role in controlling various metabolic and signaling pathways . Since metals have redox properties and rich coordination chemistry, they are capable of moving out of these controlled mechanisms and binding to other compartments, like cell constituents and designated tissue, resulting in the replacement of other metals from their natural binding sites.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…57 Its therapeutic potential, however, is limited by its nephrotoxicity. 58 Ferroptosis has been investigated as a potential mechanism for cisplatin-induced renal injury. 3 Cisplatin treatment augmented the concentration of renal ferrous iron by increasing iron content and expressions of ferritin and transferrin receptor-1 in the kidney of mice.…”
Section: The Role Of Ferroptosis In Cisplatin-induced Nephrotoxicitymentioning
confidence: 99%